Evaluation of chronic anterior knee pain in Iranian teenagers - Mahdi Motififard; Mohammad Javdan; Mahdi Teimouri; Mohammad Amin Eshaghi (Vesnu Publications, 2010)
<!-- /* Font Definitions */ @font-face {font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:1; mso-generic-font-family:roman; mso-font-format:other; mso-font-pitch:variable; mso-font-signature:0 0 0 0 0 0;} @font-face {font-family:"B Zar"; panose-1:0 0 4 0 0 0 0 0 0 0; mso-font-charset:178; mso-generic-font-family:auto; mso-font-pitch:variable; mso-font-signature:8193 -2147483648 8 0 64 0;} /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; text-align:right; mso-pagination:widow-orphan; direction:rtl; unicode-bidi:embed; font-size:12.0pt; font-family:"Times New Roman","serif"; mso-fareast-font-family:"Times New Roman"; mso-bidi-language:AR-SA;} p.abst, li.abst, div.abst {mso-style-name:abst; mso-style-unhide:no; margin-top:3.0pt; margin-right:0cm; margin-bottom:0cm; margin-left:0cm; margin-bottom:.0001pt; text-align:justify; mso-pagination:widow-orphan; direction:rtl; unicode-bidi:embed; font-size:10.0pt; mso-bidi-font-size:11.0pt; font-family:"Times New Roman","serif"; mso-fareast-font-family:"Times New Roman"; mso-bidi-font-family:"B Zar";} .MsoChpDefault {mso-style-type:export-only; mso-default-props:yes; font-size:10.0pt; mso-ansi-font-size:10.0pt; mso-bidi-font-size:10.0pt;} @page Section1 {size:612.0pt 792.0pt; margin:72.0pt 72.0pt 72.0pt 72.0pt; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0;} div.Section1 {page:Section1;} --> Introduction: Chronic anterior knee pain is one of the most common complaints, especially in our society. It consists of a large number of patients in orthopedic clinics. This pain might have serious negative effects on students' educations, on the other hand, limits their physical activities that is essential for their age. In contrast to adults, such pain etiologies may vary in many ways for teenagers. Some are easily curable and others not. In time evaluation and diagnosis can lead to a faster and more efficient treatment. The aim of this study was to evaluate chronic anterior knee pain in Iranian teenagers. Materials and Methods: In this cross-sectional study, among patients referred to Isfahan Hospitals from December 2005 to December 2007, 198 teenagers (8 to 18 years-old) who suffered from untreated chronic anterior knee pain were enrolled. All of them were examined by an orthopedic specialist. The patients' demographic information such as age, sex, physical activity type, underlying diseases if any, knee trauma history if any, pain duration, laboratory and radiological findings, and other diagnostic findings and the final diagnosis were recorded in questionnaires. Then, the relations between disease etiology and these factors were sought. Results: Chronic anterior knee pain was more frequent in boys compare with girls (53.1% vs. 46.9%). At the ages around puberty, chronic anterior knee pain was more common. The most prevalent etiologies were patella-femoral dysplasia, malalignment of lower limbs, knee menisci and ligaments tearing, osgood-schlatter disease, juvenile rheumatoid arthritis (JRA) and osteochondritis dissecans, respectively. Conclusion: In our study like many other ones, patella-femoral dysplasia and malalignment of lower limbs are the most prevalent causes among other etiologies. Such causes like malalignment of lower limbs and JRA are found more in girls and osgood-schlatter disease and osteochondritis dissecans are more common in boys. JRA and osteochondritis dissecans were considered as rare causes for chronic anterior knee pain; however in our study they played an important role. Finally we can diagnose these causes and treat them properly by this mean, we'll be able to teach the patients how to prevent such diseases